The utility of 24-h electrocardiogram recordings for the prediction of a sufficient number of premature ventricular complexes and mapping strategy during catheter ablation - Stine Aagaard-Nilsen; Stine Aagaard-Nilsen; Stine Aagaard-Nilsen; Lars Andreas Dejgaard; Lars Andreas Dejgaard; Ole-Gunnar Anfinsen; Erik Lyseggen; Torbjørn Holm; Trine S. Fink; Hans Henrik Odland; Knut Sevre; Erik Kongsgård; et al. (Frontiers in Cardiovascular Medicine)
Background and aimsAn insufficient number of premature ventricular complexes (PVCs) during catheter ablation (CA) may prohibit adequate mapping of the site of origin. Parameters to predict this situation have not been established. Our objective was to quantify the association between preprocedural information and the probability of a sufficient number of PVCs for adequate mapping and successful CA.MethodsClinical characteristics and results from examinations and procedural data were collected retrospectively from health journals for patients admitted for CA of PVCs from 2011 to 2020.ResultsIn total, 46 of 332 patients (14%) had an insufficient number of PVCs to enable adequate electroanatomical mapping. Patients with a sufficient number of PVCs had nominally more PVCs in the 24-h electrocardiogram (ECG), with a strong statistical trend [16,007 (6,509–26,205) vs. 8,332 (3,066–20,974), p = 0.055]. The receiver operator curve for a sufficient number of PVCs in 24-h ECGs had an area under the curve of 0.610 (95% CI 0.498–0.722, p = 0.055). The best predictive values were found at >10,000 PVCs per 24-h, with a positive predictive value of 67% and a negative predictive value of 57%. Patients for whom activation mapping was used as the sole mapping method had more PVCs in the 24-h ECG than did patients for whom pace mapping was added or used as an alternative [19,769 (10,564–30,526) vs. 15,237 (6,000–25,033), p = 0.022]. Neither acute outcome nor procedure time depended on the mapping strategy.ConclusionThe number of PVCs in a 24-h ECG was moderately associated with the presence of a sufficient number of PVCs to perform electroanatomical mapping during CA. The presence of more PVCs in the preprocedural 24-h ECG was associated with the use of activation mapping as the sole mapping strategy.